Learner Experience in Technology-Enhanced Education: A Conceptual Framework of Design and Evaluation - Silva, Deivid; Conte, Tayana; Valentim, Natasha (Anais Estendidos do Congresso Brasileiro de Informática na Educação (CBIE); 2025: Anais Estendidos do XIV Congresso Brasileiro de Informática na EducaçãoDO - 10.5753/cbie_estendido.2025.13329, 2025)
Learner Experience (LX) refers to learners’ perceptions and responses when interacting with educational activities supported by computational resources. The problem is that LX elements are often addressed implicitly, creating misalignment between planned activities and learners’s actual experiences. Thus, the goal of this thesis was to develop the LEDEF framework. The methodology was grounded in the Design Science Research paradigm and involved systematic mapping studies, feasibility studies, and case studies. The main results include 12 publications and the development of three technologies aimed at supporting educators, designers, and researchers. This research advances the continuous improvement of LX.